Study guides

☆☆

Q: Factor 9x squared - 6xy plus y squared - 81?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

9x+27 = -81 9x = -81-27 9x = -108 x = -12

X = 81 sqrt(X) + 3 = 12 ( subtract 3 from each side ) sqrt(X) = 9 (square both sides ) X = 81 ( the square root of 81 is 9 )

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals", "squared", "cubed". There appear to be several expressions: -2x, 2-9x, 4x and 2-81 all of which are defined.

9x9=81

Related questions

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)

The answer? There is no "answer" There cannot be an answer because they are all different. In order to make calculations, the variables have to be the same. x squared, xy, y squared are the variables, and none of them match. Therefore your "answer" must look like this: 9x squared - 6xy + y squared - 81. Hope I Helped :D

(3x - y)(3x - y) - 81

9x^2-6xy+y^2 = (y-3x)^2 (y-3x)^2-81 -> ((y-3x)+9)((y-3x)-9)

(3x - y + 9)(3x - y - 9)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 (since the first three terms make a perfect square = (3x - y - 9)(3x - y + 9) since the expression now is a difference of two squares.

(2x - 9)(2x - 9) or (2x - 9)2

(3x - y - 9)(3x - y + 9)

(9x)2 +9x/(45x)2 +81= 9+9x/86

x2-81 = (x-9)(x+9)

(9 - 5u)(9 + 5u)

People also asked